Sprint Training Versus Hollow Sprint : Which Method is Better on Base Running Speed - Fathoni, Amirudin; Rachman, Hari Amirullah (Department of Physical Education, Sport, Health and Recreation, 2019)
This study aims at knowing the effect of sprint training and hollow sprint exercises on running speed of base running and knowing which method is better between sprint training and hollow sprint on base running speed for male students of softball extracurricular class X at SMK Bhina Karya Karanganyar. An experimental study proposed with the subjects of 32 male students of softball extracurricular. The data analysis technique used the difference test (t-test) by doing a reliability test, normality test, and homogeneity test. Based on the results, it found there was the effect of sprint training and hollow sprint exercises on running speed of base running in subject with increased training sprint = 2.07s and increase in hollow sprint = 0.53s; sprint training is better than hollow sprints for running base speed with an increase = 14.3%> while increase in hollow sprint = 3,67%. Thereupon (1) there was the influence of sprint training and hollow sprint on running speed of base running in male students of softball extracurricular class X at SMK Bhina Karya Karanganyar; (2) sprint training is better than hollow sprints for running speed of base-running for male students of softball extracurricular class X at SMK Bhina Karya Karanganyar.